Transgenic expression of human leukocyte antigen‐E attenuates GalKO.hCD46 porcine lung xenograft injury. (3rd March 2017) - Laird, Christopher T.; Burdorf, Lars; French, Beth M.; Kubicki, Natalia; Cheng, Xiangfei; Braileanu, Gheorghe; Sun, Wenji; O'Neill, Natalie A.; Cimeno, Arielle; Parsell, Dawn; So, Edward; Bähr, Andrea; et al.
Abstract: Background: Lung xenografts remain susceptible to loss of vascular barrier function within hours in spite of significant incremental advances based on genetic engineering to remove the Gal 1, 3‐αGal antigen (GalTKO) and express human membrane cofactor protein (hCD46). Natural killer cells rapidly disappear from the blood during perfusion of GalTKO.hCD46 porcine lungs with human blood and presumably are sequestered within the lung vasculature. Here we asked whether porcine expression of the human NK cell inhibitory ligand HLA‐E and β2 microglobulin inhibits GalTKO.hCD46 pig cell injury or prolongs lung function in two preclinical perfusion models. Methods: Lungs from pigs modified to express GalTKO.hCD46 (n=37) and GalTKO.hCD46.HLA‐E (n=5) were harvested and perfused with human blood until failure or elective termination at 4 hours. Airway pressures and pulmonary artery hemodynamics were recorded in real time. Blood samples were also collected throughout the experiment for analysis. Porcine aortic endothelial cells (PAECs) from each genotype were cultured in monolayers in microfluidic channels and used in fluorescent cytotoxicity assays using human NK cells. Results: HLA‐E expression on GalTKO.hCD46 PAECs was associated with significantly decreased antibody‐dependent and antibody‐independent NK‐mediated cytotoxicity under in vitro conditions simulating physiologic shear stress. Relative to GalTKO.hCD46 pig lungs perfused with human blood on an ex vivo platform, additional expression of HLA‐E increased median lung survival (>4 hours, vs 162 minutes, P =.012), and was associated with attenuated rise in pulmonary vascular resistance, and decreased platelet activation and histamine elaboration. As expected, HLA‐E expression was not associated with a significant difference in NK cell adhesion to endothelial cells in vitro, or NK cell and neutrophil sequestration during organ perfusion. Conclusions: We conclude human NK cell activation contributes significantly to GalTKO.hCD46 pig endothelial injury and lung inflammation and show that expression of HLA‐E is associated with physiologically meaningful protection of GalTKO.hCD46 cells and organs exposed to human blood.